การพัฒนารูปแบบการนิเทศการสอนเพื่อพัฒนาสมรรถภาพการจัดการเรียนรู้ของครูตามทักษะการเรียนรู้ในศตวรรษที่ 21 ของสถานศึกษาในสังกัดเทศบาลนครตรัง THE DEVELOPMENT OF THE INSTRUCTIONAL SUPERVISION MODEL FOR STRENGTHENING THE TEACHERS’ ABILITY IN THE 21ST CENTURY LEARNING SKILLS OF THE MUNICIPALITY SCHOOLS IN TRANG - สงอาจินต์, ศิลา; ชัยเรือง, นพรัตน์; ชูช่วยสุวรรณ, จำเริญ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2019)
The objectives of this research were 1) to study and analyze the basic information and the requirement of school’s administrator and teacher in order to increase the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century, 2) to create the Model of the class observing to increase the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century of schools under Trang municipality, 3) to test the pattern of the class observing to increase the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century of schools under Trang municipality, and 4) to evaluate the result and to improve the pattern of the class observing to increase the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century of schools under Trang municipality. The target group included 21 supervising teachers and 136 supervised teachers. The data were analyzed by frequency, percentage, mean, standard deviation, t-test (dependent) statistic and content analysis. This research’s result according to the study of information from document resource, consisting of basic policy information, basic information and requirement of school’s administrators and teachers revealed that schools, teachers and educational personnel had more knowledge and ability in education to pass on to the student’s academic excellence and learning activity method. The students could develop the self-study and knowledge searching with teacher to give them advice and create the activity that allowed the students to evaluate their own development. The content of the main subjects should be intensified and enhanced with the learning skills in the 21st century. Moreover, the ability of teachers under Trang municipality should be developed, using the class observing to improve the learning activity. The class observing pattern to increase the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century of schools under Trang municipality were applied in “APPIE Model” which consists of 5 steps; 1) estimate the requirement 2) plan the class observing 3) educate before observing 4) process the observing and 5) evaluate the observing’s result. The implementation of the model was attend training supervising teachers and supervised teachers on 21st century learning management techniques. The evaluation of the model found to be in the high level. The evaluation of the ability to supervise of the supervising teacher to the teacher’s efficiency in creating the learning activity according to the learning skills in the 21st century’s result was in the high level in average. The evaluation of the supervised teacher’s knowledge and understanding in learning activity in the 21st century’s result was in the high level. The evaluation of the supervised teacher’s efficiency to create the learning activity in the 21st century’s result is in the high level. The evaluation of the supervising teachers and supervised teachers’ satisfaction to the class observing pattern to increase the teachers’ efficiency in creating the learning activity according to the learning skills in the 21st century’s result was in the high level.